Mixed molybdenum and vanadium oxide nanoparticles with excellent high-power performance as Li-ion battery negative electrodes. (1st November 2019) - Bauer, Dustin; Ashton, Thomas E.; Brett, Dan J.L.; Shearing, Paul R.; Matsumi, Noriyoshi; Darr, Jawwad A.
Abstract: Several nano-sized mixed molybdenum/vanadium oxide monoclinic solid solutions were synthesised using a continuous hydrothermal flow process and studied with a wide range of physical characterization techniques including X-ray photoelectron spectroscopy, X-ray diffraction, transmission electron microscopy and X-ray absorption spectroscopy. The nanomaterials were tested as anodes for Li-ion batteries in the potential range 0.05–3.00 V vs. Li/Li + . Samples with nominal formulas of Mo0.5 V0.5 O2 and Mo0.33 V0.67 O2 showed excellent performance, especially at high current rates, due to their highly pseudocapacitive charge storage mechanism. At a specific current of 10 A g −1, Mo0.5 V0.5 O2 and Mo0.33 V0.67 O2 showed specific capacities of ca. 200 and 170 mAh g −1, respectively. Mo0.5 V0.5 O2 also showed good cyclability, with a specific capacity of 480 mAh g −1 after 150 cycles at a specific current of 0.5 A g −1 . For cyclic voltammetries conducted at high scan rates, pseudocapacitive charge storage contributed more than 90% to the total charge storage for both samples. The scalability of the synthesis technique and excellent electrochemical performance at high power, make these materials promising as negative electrode active materials for Li-ion batteries.